Consulate general of the Republic of Indonesia Davao City’s programs to increase the nationalism of the Indonesian School of Davao’s Students in 2022-2023 - Faaliha, Moza; Azizah, Nur (Universitas Islam Malang, 2024)
Indonesia and the Philippines are two countries that share direct borders. However, problems arose when the two countries set national boundaries after independence. Conditions like this affect the nationalism of Indonesian citizens living on the border, especially the younger generation. This research aims to determine the program of the Consulate General of the Republic of Indonesia Davao City in increasing the sense of nationalism of students at the Indonesian School of Davao. This research uses descriptive qualitative methods with data originating from journals, observations, social media, news and interviews conducted with the Davao Indonesian School, namely the principal, 2 teachers and 10 students who are citizens of Indonesian descent. In this research, it shows the programs that have been carried out by the Consulate General of the Republic of Indonesia Davao City to increase the sense of nationalism of the students of the Indonesian School of Davao, such as the introduction of Indonesian language and culture, competitions and inspirational talks, as well as the existence of rules or regulations that require students to speak Indonesian. This program was quite effective in increasing the sense of nationalism among the students at the Indonesian School of Davao.